Investigating the limits of hard X-ray coherence length measurement employing Young’s double slit experiment - Rielly Castle; Narayan Appathurai; Nicholas Simonson; Yasaman Sigari; Mark J. Boland; Feizhou He; Chithra Karunakaran; Jian Wang; Beatriz D. Moreno; Venkata S. C. Kuppili (Scientific Reports)
Abstract Young’s double slit experiment has been the most explored technique to gauge a system’s coherence properties. The limits of this technique in characterizing spatial coherence properties of high emittance, hard X-ray synchrotron sources have been performed at the BXDS-IVU beamline, Canadian Light Source (CLS). High emittance synchrotron sources have been assumed to possess sub-optimal coherence properties. While this is largely true, it’s important to understand the limits of coherence for these sources. We demonstrate that the Young’s double slit experiment has harsher limits than what is normally expected. We present data obtained at multiple energies in both spatial directions leading to a thorough understanding of the limitations of employing Young’s double slit experiment to characterize low coherence length systems. We propose a numerical technique to estimate the source size directly from the double slit interference patterns. With these results, we have demonstrated that CLS has functional coherent beam properties in the hard X-ray regime with spatial coherence lengths ranging from 5.37 to 17.61 µm in the horizontal direction. The spatial coherence lengths in the vertical direction were at least 3 times larger. Finally, we present theoretical calculations showcasing the limits of Young’s double slit experiment in characterizing diffraction limited sources.